Selectivity Of Candida Rugosa Lipase Immobilized Onto Layered Double Hydroxides As Catalyst In Synthesis Of Fatty Acid Esters - Abdul Rahman M.B.; Othman S.S.; Md Yunus N.M. (Penerbit UTM Press, 2024)
Indexed by WOS/ Scopus